2021
DOI: 10.1109/jsen.2020.3000301
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Method Based on Time Reversal and Optimization Techniques for Locating Faults on Power Grids

Abstract: Electromagnetic time reversal (EMTR) has recently emerged as a promising technique applied for locating faults in power networks. It directly transposes the idea of focusing energy back to its source introduced in original time-reversal (TR) methods. Accordingly, we present in this paper, FasTR, a method based on the tenets of TR, that estimates the fault location by employing optimization based algorithms for fetching the highest peak amplitude with maximum coherence in space and time. However, it uses an alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A similar effort to accelerate the backward-propagation process led to the so-called FasTR method Kafal et al (2021a).…”
Section: Focusing/location Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar effort to accelerate the backward-propagation process led to the so-called FasTR method Kafal et al (2021a).…”
Section: Focusing/location Metricsmentioning
confidence: 99%
“…Different types of full-scale experiments, including field experiments and pilot tests, have been performed worldwide in the past years, with particular attention to assessing the fault location performance of the EMTR method in real power-system environments. So far, three experimental studies have been reported in the literature Wang et al (2018a), Wang et al (2020b), Kafal et al (2021a). Note that a series of reduced-scale experiments in laboratory environments were also conducted during the same period, providing a preliminary validation of some of the foregoing EMTR fault location metrics [e.g., Razzaghi et al (2013a), He et al (2018)].…”
Section: Experimental Study Of Electromagnetic Time Reversal-based Fa...mentioning
confidence: 99%
“…Thanks to the TR invariance of the transmission-line equations and the inherent spatial focusing property of the TR invariant system, FasTR has emerged as a promising technique for detecting and locating faults in power systems [19]. With a limited knowledge of the tested network and a moderate need for computing resources, FasTR follows a similar analogy to EMTR based methods but uses a different post-processing approach for locating the fault.…”
Section: Fastr In a Nutshellmentioning
confidence: 99%
“…Within the same context, a recent proposal for fault location in power grids is FasTR [19], a method also inspired from the idea of TR focusing. Thanks to a simplified analytical model that computes the voltage (or the current) at any position and any instant of the network under test (NUT), FasTR gets rid of the ponderous simulation stage endured by EMTR [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation